The distribution of information about the year of ethnographic regions within information space - Petreikis, Tomas (Information & Media, 2017)
One of the main problems of modern society is the proper organisation of how information is distributed and made to appear public. In 2015, the Year of Ethnographic Regions program revealed the experience of participants in the public sector. The idea behind the Year of Ethnographic Regions and its program of events have attracted widespread public support and involvement. The total number of 437 events have been recorded and analysed in this study. The program of events covered the entire country, involved Lithuanian residents in different social, age and geographical groups. Due to ethnic specifics, the engagement was greater in the rural regions and lower in the cities. Without objective funding, the organisers of events relied on the proven performance of public communication strategies and accumulated experience. Most of the information about the events was published on various content websites (320 events), periodicals (261) and the web pages of daily newspapers (223). Less information was published on social media (127 events), television (28) and radio (7). Many budget and public event organisers had a channel for distributing information, managed by themselves, so they were able to publish at least the basic information concerning the events. The local media (periodicals, institutional websites etc.) had the biggest impact by informing the population. Social media resources, the influence of which will increase in the future, were properly unused, so it is time to pay due attention to social media opportunities of publicity. A lack of the following aspects was observed: the coordination of activities, proper inter-institutional cooperation, involvement of the national media, the President of the Republic of Lithuania and the publishing industry, the feasibility of new communication channels (e.g., calendars of events). The program of the Year of Ethnographic Regions, with its abundance of events, serves as a good example for evaluating the experiences and gaps that should be filled in the future by improving the quality of public communication and ensuring the proper distribution of information to the public.